ALBA-TCP: Towards New Mechanisms for Participation in the Social and Solidarity Economy - Schaposnik, Carmen Rosa; Pardo, Eugenia Candelaria (Cooperativismo & Desarrollo, 2015)
Purpose: The alba-tcp is a regional integration initiative promoted by former president Hugo Chávez Frías that introduces the innovation of contemplating a new type of social agenda in its mechanisms and instruments for cooperation. This becomes significant in a world convulsed by the global crisis of 2007-2008 stemming from speculative action by concentrated groups that destabilize economies at the worldwide scale; also, in regions such as Latin America and the Caribbean, where there are divergent visions of regional integration. Description: The article first of all proposes to review social participation in the institutions of the alba-tcp; it then examines mechanisms for insertion of the social and solidarity economy; and finally, it seeks to identify the challenge posed by this new type of social agenda. Point of view: From a descriptive-interpretive perspective, it shows the intellectual tension proposed by this model for integration along with the possibilities that are opened for the social and solidarity economy. Conclusions: The aim is to reflect, based on recognition of a conflictive and open reality conditioned by the territory, regarding the need for joint work by scientists with the peoples.